In vitro cytotoxic and ultrastructural effects of selected carboxylic ionophores on cardiac and skeletal myoblasts - Botha, C.J. (Christoffel Jacobus) (University of Pretoria, 2023)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2022.